TOURISM AND DISASTER: THE REVIEW OF GOVERNMENT POLICY TOWARD THE IMPACT OF NATURAL DISASTER ON TOURISM INDUSTRY PERFORMANCE - Erda Rindrasih (ASEAN Journal on Hospitality and Tourism, 2015)
Bogor Over the last decade, a number of disaster have affected Indonesia as the tourist destination. This article provides the analysis of the relation between tourism and disaster and frames the impact of natural disaster (hazards) to the performance of tourism industry in Indonesia under the perspective of sustainable development. It shows that Indonesian Government prepare the strategy to cope with the natural disaster but low response in tourism sector recovery. The article concludes that since tourism is very vulnerable sector, which mainly influence by the internal aspect and external aspect, the need of crisis management related to natural disaster is needed.